2020
DOI: 10.3390/v12101083
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Development, Epilepsy, and the Pharmacotherapy Approach in Children with Congenital Zika Syndrome: Results from a Two-Year Follow-up Study

Abstract: Clinical outcomes related to congenital Zika syndrome (CZS) include microcephaly accompanied by specific brain injuries. Among several CZS outcomes that have been described, epilepsy and motor impairments are present in most cases. Pharmacological treatment for seizures resulting from epilepsy is performed with anticonvulsant drugs, which in the long term are related to impairments in the child’s neuropsychomotor development. Here, we describe the results from a two-year follow-up of a cohort of children diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The head circumference at birth for children with microcephaly has also been associated with severe neurodevelopmental delay, severe neuroimaging findings, dysphagia, spasticity, hyperreflexia, hearing loss and epilepsy, according to the Garcia-Boyano et al (2020) cohort study [ 33 ]. A cohort study of Quilião et al published in 2020 [ 34 ] describes the findings of a cohort of children with CZS in terms of their head circumference and neurological-neurodevelopmental outcomes. The results showed that the majority of children with severe microcephaly developed motor dysfunction and/or epilepsy, compared to children who were normocephalic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The head circumference at birth for children with microcephaly has also been associated with severe neurodevelopmental delay, severe neuroimaging findings, dysphagia, spasticity, hyperreflexia, hearing loss and epilepsy, according to the Garcia-Boyano et al (2020) cohort study [ 33 ]. A cohort study of Quilião et al published in 2020 [ 34 ] describes the findings of a cohort of children with CZS in terms of their head circumference and neurological-neurodevelopmental outcomes. The results showed that the majority of children with severe microcephaly developed motor dysfunction and/or epilepsy, compared to children who were normocephalic.…”
Section: Resultsmentioning
confidence: 99%
“…Severe neurological and neurodevelopment outcomes were a more frequent sign in children born with microcephaly. More specifically, there is a strong correlation between the severity of the outcomes with a lower birth head circumference [ 26 , 28 , 29 , 30 , 31 , 34 ]. Of course, microcephaly of any type is considered a major driver of neurology and neurodevelopment delays [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Quilião et al ‘s study [ 23 ], among the 11 evaluated children, 8 presented acute microcephaly associated with motor disability and/or epilepsy. It was observed that children with less motor impairment had minor relative change in head circumference, normal electroencephalogram tracing and absence of seizures [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Quilião et al ‘s study [ 23 ], among the 11 evaluated children, 8 presented acute microcephaly associated with motor disability and/or epilepsy. It was observed that children with less motor impairment had minor relative change in head circumference, normal electroencephalogram tracing and absence of seizures [ 23 ]. In this study, 100% of children with GMFCS classification I and II had lower values of Z score of cephalic perimeter when compared to other classifications and the patients with more acute GMFCS levels were more likely to be epileptic.…”
Section: Discussionmentioning
confidence: 99%
“…Although most fetuses with prenatal ZIKV exposure present no detectable clinical anomalies, a subset of congenitally infected offspring can have mild, moderate or severe adverse outcomes 2 collectively referred to as congenital Zika syndrome (CZS) 3 , 4 . The CZS phenotype encompasses a wide spectrum of structural anomalies (e.g., cortical atrophy with microcephaly 5 ), functional impairments (e.g., dysphagia 6 ), and clinical sequelae (e.g., epilepsy 7 , 8 ) that may manifest either at birth or in early life 9 . The prognosis for live births with CZS is not fully described; however, the most severe phenotype seems to be associated with first-trimester exposure 10 and one important prognostic factor is the severity of microcephaly 11 .…”
mentioning
confidence: 99%